2019
DOI: 10.29261/pakvetj/2018.091
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of ESBL-Producing-Escherichia coli in Poultry Farm Environment and Retail Poultry Meat

Abstract: Antimicrobials are excessively used in Pakistan during broiler poultry production, however, status of antimicrobial resistance (AMR) is not known. We report on the frequency of extended spectrum β-lactamase (ESBL)-producing-Escherichia coli recovered from samples obtained from poultry farm environment (n=100) and chicken meat samples (n=100) collected at sales point of live bird market in District Peshawar, Pakistan. Phenotypically confirmed ESBL producers were further investigated for the presence of ESBL-and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 28 publications
5
16
2
Order By: Relevance
“…A possible explanation for the difference between studies carried out in northern Nigeria and our study could be due to the sample types collected as our study isolated E. coli from freshly dropped chicken faecal samples as opposed to cloacal swabs. A study conducted in Pakistan, reported a slightly higher E. coli prevalence of 36% from the poultry farm environment when compared to 26.1% obtained from poultry environment in the present study [35]. Our study ndings are consistent with the reports of a related study carried out in the poultry farm environment in Egypt where E. coli prevalence of 26.8% was obtained from the farm environment [36].…”
Section: Discussionsupporting
confidence: 91%
“…A possible explanation for the difference between studies carried out in northern Nigeria and our study could be due to the sample types collected as our study isolated E. coli from freshly dropped chicken faecal samples as opposed to cloacal swabs. A study conducted in Pakistan, reported a slightly higher E. coli prevalence of 36% from the poultry farm environment when compared to 26.1% obtained from poultry environment in the present study [35]. Our study ndings are consistent with the reports of a related study carried out in the poultry farm environment in Egypt where E. coli prevalence of 26.8% was obtained from the farm environment [36].…”
Section: Discussionsupporting
confidence: 91%
“…However, use of antibiotics in poultry industry is also not strictly regulated (Mitema, 2010) raising concern of emergence of AMR. Antimicrobial resistant E. coli have been increasingly reported from food producing animals (Ali et al, 2017;ur Rahman et al, 2018a;ur Rahman et al, 2018b). The current study reports on the CPE recovered from retail poultry meat raising concern of its dissemination.…”
Section: Discussionmentioning
confidence: 90%
“…Despite the fact that antimicrobials are not strictly regulated in Pakistan and generous availability of antibiotics cheering its misuse and pumping selective pressure for the emergence of antimicrobial resistance, literature data regarding overall antimicrobial resistance surveillance is totally missing in the country with random reports suggesting widespread and high level of resistance against cephalosporins, sulfonamides and carbapenem drugs (Perry et al, 2011;Sattar et al, 2016;Adnan et al, 2017;ur Rahman et al, 2018b). To the best of our knowledge, no signal report is published from Khyber Pakhtunkhwa, Pakistan regarding the status of carbapenemase-producing Enterobacteriaceae associated with poultry meat in Pakistan.…”
Section: Research Articlementioning
confidence: 99%
“…Patterns of usage of antibiotics in food producing animals in Pakistan: Unfortunately, in Pakistan, AMU in food-producing animals is unregulated and there is no estimation of annual usage. AMR is one of the major health challenges in Pakistan (Levy, 2002a;Goossens et al, 2005;Ali et al, 2010;Idrees et al, 2011;Khan et al, 2013;Adnan et al, 2017;Mohsin et al, 2017;Rahman et al, 2018b). Although, it is hard to find the exact amount of antibiotics being used for treatment, prevention and as growth promoters in FPAs in Pakistan, nevertheless, practices and trends at commercial as well as domestic level indicate that major share of antibiotic usage is aimed for disease prevention and as growth promoters and is offered as supplements on routine basis [https://www.dawn.com/ news/1245840].…”
Section: Development Of Amr and Its Impactmentioning
confidence: 99%